Peer online training (POT) as learning activity in computer security audit and risks management teaching module - Ahmad, Rabiah; Hassan, Aslinda; Hsiung, Lee Hwee; Othman, Mohd Fadzrin (2023)
Teaching and Lecturing Computer Security Audit & Risks Management module is challenging. With the increase demand of high skilled talent in computer security by industries, all subjects at Bachelor Degree Program are required to be up to date and complete with practical skill training. Many technical universities in Malaysia promote Practical Application Oriented Approach (PAO) as mode of delivery in teaching and learning. As we know, an online learning received serious attention due to pandemic Covid 19. Inspired from Professional Training in Cybersecurity, we implemented method call Peer Online Training (POT) as learning activity in teaching Computer Security Audit and Risks Management module. There are ten (10) students were given a task to conduct mini project related to ISMS, risks analysis and Incident Management. The project required students to conduct information searching, practical exercises and industry communications. Students need to utilize their skill in Microsoft Power point, Infographics, and Multimedia applications for developing a Training Contents. Each training video uploaded to Youtube Channel and the link shared among themselves. We also share the Youtube link to five panels from industry for content validations. The panels are from Cybersecurity Malaysia, Finance Officer at Higher Institution, and Inland Revenue ICT Director. All students were asked to participate for physical training and technique called “Ireland Hopping” were applied to improve training contents. The training also required students to conduct self and peer assessment. We observed students’ performance by (1) distributing feedback survey form and (2) personal interview. The results show that 95% students enjoyed Peer Online Training. Their feedback shows that POT increased understanding and improve their skill to explore audit activity. They recommended for more on online practical exercise in future. We concluded that POT able to act as value added tool in learning activity. It creates new insight for students to have better understanding in learning Computer Security Audit & Risk Management.